A review of effective essential oils and their biologically active compounds to protect the safety of food stored against insect pests. Issue 2 (4th March 2022) - Moshrefi Zenoozi, Zahra; Soltaninezhad, Batool; Hashemi, Mohammad; Noori, Seyyed Mohammad Ali
ABSTRACT: With population growth and the increasing human demand for crops, chemical insecticides have been used to reduce pests. Due to the adverse effects of these chemicals on the environment and health, several studies have investigated alternatives such as natural insecticides derived from essential oils or plant extracts. This review article was provided by using search engines such as Google scholar, Science Direct and PubMed. The compounds found in essential oils and plant extracts affect a wide range of insects. The most effective biologically active substances in these extracts are 1–8 cineole, thymol, eugenol, limonene, carvacrol, and terpenes such as limonene, pinene and myrcene. Furthermore, aromatic plants have the most remarkable impact on food pests owing to high concentrations of biologically active substances. Plant secretion of aldehydes could also remove insects although further studies are required. Overall, natural and safe insecticides could be produced by extracting bioactive materials from plants.